Errata to “A Survey of Multiattribute Utility Theory and Applications” - Farquhar, Peter H. (Management Science, 1978)
List of typographical errors that appeared in my paper “A Survey of Multiattribute Utility Theory and Applications” in M. K. Starr and M. Zeleny (eds.), Multiple Criteria Decision Making, TIMS Studies in the Management Sciences, vol. 6, North-Holland, Amsterdam, 1977, pp. 59–89.